THE CONSUMER ACCEPTANCE ON THE MEAT BALL PROCESSED BY USING THE DRIED SMALL SHRIMP (Acetes erythtraeus) COMPARED TO THE FRESH ONEAS THE RAW MATERIALS - Rafika Monaliza; Suparmi Suparmi; Mery Sukmiwati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT      This study was purposed to determine the consumer acceptance of small shrimp meat ball using dried and fresh raw material of smallshrimp (Acetes erythtraeus).The research method used was a comparative-experimental method and analyzed by using T test to compare the using of dried shrimp meatballs and the fresh one. The parameters used were organoleptic evaluation (color, texture, flavor and taste) and chemical analysis (the content of water, protein and fat). The results showed that the meat ball using the dried shrimp as the raw material was indicating more accepted by the consumers,at the rate of 62.19%, rather than using the fresh one.The product was characterized to yellowish gray color, typical aroma of shrimp, coarse fiber texture and contained water 41.16%, protein 23.36%, and fat 8.67%.            Key words:Acetes erythraeus, Consumer, Small shrimp